Pengaruh Latihan Aerobik Terhadap Jumlah Trombosit Pada Mahasiswa Program Studi Keperawatan Baturaja Tahun 2012 - SUPARNO SUPARNO (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2014)
Platelets are fragments or fragments of megakaryocyte cytoplasm not cored from a size 1-4 microns and circulate in the blood circulation for 10 days. Platelets play an important role in the formation of blood clots. Physical exercises are conducted regularly to improve one's health. Aerobic exercise is considered beneficial, but the sport is sometimes causing sudden cardiac death. The study of the mechanism of the effect of aerobic exercise on arterial thrombosis is very important, not only for the prevention of cardiovascular events but also for sporting activities are safe for health. The purpose of this study was to see the effect of aerobic exercise on platelet counts in the Student Nursing Program Balfour.